Kompetensi Seorang Guru dalam Mengajar - Alifia Mutsla Fakhruddin; Annisa Annisa; Lesi Oktiani Putri; Putri Rizqi Aura Tanzilla Sudirman (Journal on Education, 2023)
Teacher competence is a set of knowledge, skills, and behaviors that must be possessed, internalized, and mastered by teachers in carrying out their professional duties. Teacher competencies as learning agents at the primary and secondary education levels as well as early childhood education are: pedagogic, personality, professional, and social competencies. With skill requirements, a teacher must master the skills covering: opening and closing lessons, asking questions, providing reinforcement, and conducting various teaching. In the teaching and learning process, the teacher also acts as a director as well as an actor. This factor is very important so that it is expected to determine the success of the teaching and learning process in the classroom. The type of research used is a literature study with a descriptive qualitative type of research. The results of the study obtained that the competence possessed by a teacher in teaching greatly affects the learning outcomes of students.